Here's where parentheses come in handy.
As written, the identity is wrong. What you meant to say was
(csc^3 - csc + cot)/csc
= (csc(csc^2 - 1) + cot)/csc
= (csc cot^2 + cot)/csc
= csc cot^2/csc + cot/csc
= cot^2 + cos/sin * sin
= cot^2 + cos
Prove trig identity - Prove the following trigonometric identity: (sec^2x-1)(csc...
Math- gr.12 Trig. - Hi, could someone explain to me how to use a counterexample...
Trig - Prove that the equation is an identity: cot4theta - csc4theta = -cot sq ...
trig - Prove the following trig identity: 1 + sinx = sinx(1+cscx)
trig - cos(sin^-1 x)=sq rt(1-x^2) prove the identity
trig - sinx+sinxcot^2x=cscx prove each identity
Math - Required to Prove the following trig identity: (cos2x)^2 + (sin2x)^2 = 1
Pre-Calc (Prove the identity) - Prove the identity. (show steps please!) Thank ...
trig - Prove the identity. (must work with left side) (1-2sin(x)^2)=(cos(x)^2)
Trig Identity - Prove or disprove the following identity sin^4theta - cos^4theta...